A T to A base substitution and small deletions in the conalbumin TATA box drastically decrease specific in vitro transcription. - Wasylyk, B (1981)
We have previously shown that a T to G transversion at the second T of the conalbumin "TATA" box drastically decreases specific initiation of transcription by RNA polymerase B (1). We now report that a T to A transcription at the same nucleotide also drastically decreases transcription, suggesting that these mutations influence transcription mainly by altering nucleotide recognition rather than helix stability. Small deletions of 2, 3 and 4 nucleotides in the "TATA" box also drastically decrease specific initiation of transcription.